Exploring the intersection of socioeconomic and environmental changes and their impact on India's lentic water systems - Pooja Singh; Tanya Nema; Basant Yadav; Abhay Raj; Ilhan Özgen-Xian (Environmental and Sustainability Indicators)
Climate change poses significant threats to lentic water bodies (LWBs) by altering precipitation patterns, raising temperatures, and intensifying extreme weather events. These changes deteriorate water quality, degrade habitats, and reduce biodiversity. This study examines the interplay between socioeconomic and environmental factors affecting LWBs in the Indian states, namely Punjab, West Bengal, Kerala, and Gujarat, with different socio-environmental conditions from 1990 to 2020. Key socioeconomic parameters include population, literacy rate (LR), density of population (DoP), and Gross Domestic Product (GDP), while environmental factors cover rainfall, temperature, greenhouse gas (GHG) emissions, and land use/land cover (LULC) changes. Pearson correlation and principal component analysis (PCA) were used to assess these factors' relationships with LWB ecosystems, and the coupling coordination degree (CCD) model evaluated coordinated development in the study area. The analysis reveals notable LULC changes, with urbanisation expanding at the cost of agricultural and barren lands, leading to habitat loss, fragmentation, and pollution. Gujarat showed a significant increase in LWB area, growing from 308 km2 in 1990 to 885 km2 by 2019. The CCD model indicates a shift from slightly unstable development (0.2 < D ≤ 0.5) to barely neutral development (0.5 < D ≤ 0.8), with Punjab achieving this by 2005, while West Bengal lagging until 2015. Socioeconomic progress across states generally lags behind environmental changes (ψ(s) < ψ(e)), indicating imbalanced development. This study underscores the urgent need for targeted LWB conservation strategies in India, addressing socioeconomic and environmental drivers to ensure sustainable water management and biodiversity preservation. Balanced interventions are critical to stabilising LWB ecosystem health.